Steel material joined body and manufacturing method thereof

By optimizing the carbon concentration gradient at the interface and heating the steel joint to specific temperatures, the method effectively enhances the tensile strength and elongation of stainless steel and chromium molybdenum steel joints.

JP2025063350APending Publication Date: 2025-04-16NETUREN CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023172420
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing methods for joining stainless steel and chromium molybdenum steel materials fail to achieve high tensile strength and elongation.

Method used

A steel joint is created by joining stainless steel and chromium molybdenum steel with a carbonaceous material, where the carbon concentration on the stainless steel side is higher than the material's concentration, and on the chromium molybdenum steel side is lower than the material's concentration, and heating them to a maximum temperature of 1300° C. and 1500° C. or less.

Benefits of technology

This method achieves high tensile strength and elongation in the steel joint, suppressing the generation of carbides at the bonding interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063350000001_ABST
    Figure 2025063350000001_ABST
Patent Text Reader

Abstract

To provide a steel material joined body and a manufacturing method thereof that can achieve high tensile strength and elongation at a joint of a stainless steel material and a chrome molybdenum steel material.SOLUTION: In a steel material joined body 1 in which a stainless steel material 10 and a chrome molybdenum steel material 20 are joined, a carbon concentration on a stainless steel material 10 side at a joint interface 30 of the stainless steel material 10 and the chrome molybdenum steel material 20 is higher than a carbon concentration of a raw material of the stainless steel material 10, and a carbon concentration on a chrome molybdenum steel material 20 side at the joint interface 30 is lower than a carbon concentration of a raw material of the chrome molybdenum steel material 20.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel member joint and a manufacturing method thereof. [Background technology]

[0002] There is known a method for manufacturing a joined steel member in which the joining surfaces of steel members to be joined via a carbonaceous material are overlapped and heated (see Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-7970 [Patent Document 2] Japanese Patent Application Publication No. 57-22867 [Patent Document 3] JP 2023-39175 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the inventions described in Patent Documents 1 to 3 have limitations in terms of achieving high tensile strength and elongation in joining between stainless steel material and chromium-molybdenum steel material. Therefore, an object of the present invention is to provide a joined steel material body that achieves high tensile strength and elongation in the joining of a stainless steel material and a chromium-molybdenum steel material, and a manufacturing method thereof. [Means for solving the problem]

[0005] The steel joined body according to the present invention is a steel joined body in which a stainless steel material and a chromium-molybdenum steel material are joined, wherein the carbon concentration on the stainless steel material side at the joint interface between the stainless steel material and the chromium-molybdenum steel material is higher than the carbon concentration of the stainless steel material, and the carbon concentration on the chromium-molybdenum steel material side at the joint interface is lower than the carbon concentration of the chromium-molybdenum steel material.

[0006] The manufacturing method of a steel joined body according to the present invention is a manufacturing method of a steel joined body in which a stainless steel material and a chromium-molybdenum steel material are joined, and includes a arranging step of arranging a carbonaceous material on at least one of the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined, a superposing step of superposing the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined with the carbonaceous material interposed therebetween, and a heating step of heating the stainless steel material and the chromium-molybdenum steel material with the superposed joining surfaces at a maximum attainable temperature of 1300°C or more and 1500°C or less. Effect of the Invention

[0007] According to the present invention, there is provided a joined steel material body that achieves high tensile strength and elongation in the joint between a stainless steel material and a chromium-molybdenum steel material, and a manufacturing method thereof. [Brief description of the drawings]

[0008] [Figure 1] FIG. 2 is a conceptual diagram for explaining a steel joint according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a process flow diagram for explaining a method for manufacturing a steel joint according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a conceptual diagram for illustrating a method for manufacturing a steel joint according to a first specific embodiment of the present invention. [Figure 4] FIG. 6 is a conceptual diagram for illustrating a method for manufacturing a steel joint according to a second specific embodiment of the present invention. [Diagram 5] 1 is an iron-carbon phase diagram (corresponding to SUS304) for explaining the effect of the present invention when the heating temperature is 1300° C. or higher. [Figure 6] 1 is an iron-carbon phase diagram (corresponding to SCM435H) for explaining the effect of the present invention at a heating temperature of 1300° C. or higher. [Figure 7] FIG. 2 is a conceptual diagram for explaining the effect of the present invention when the heating temperature is 1300° C. or higher. [Figure 8]FIG. 2 is a graph showing the results of tensile strength, elongation, and elongation-nominal stress curves in the tensile tests of the examples and comparative examples. [Figure 9] FIG. 11 is a graph showing the results of carbon content and hardness distribution at the bonding interface in the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. FIG. 1 is a conceptual diagram for explaining a steel member joint according to the present embodiment. 1, a steel joined body 1 according to this embodiment is formed by joining a stainless steel material 10 and a chromium-molybdenum steel material 20. The carbon concentration on the stainless steel material 10 side at a joint interface 30 between the stainless steel material 10 and the chromium-molybdenum steel material 20 (hereinafter also referred to as "material") is higher than the carbon concentration B of the stainless steel material 10 material, and the carbon concentration on the chromium-molybdenum steel material 20 side at the joint interface 30 is lower than the carbon concentration C of the chromium-molybdenum steel material 20 material. Specifically, the carbon concentration on the stainless steel material 10 side at the joint interface 30 has a first concentration gradient layer 15 in which the carbon concentration increases from the joint interface 30 toward the material side and then decreases (having a maximum value A). Also, the carbon concentration on the chromium-molybdenum steel material 20 side at the joint interface 30 has a second concentration gradient layer 25 in which the carbon concentration decreases from the carbon concentration C of the chromium-molybdenum steel material 20 toward the joint interface 30.

[0010] Since the joined steel member 1 according to the present embodiment has the first concentration gradient layer 15 and the second concentration gradient layer 25 at the joint interface 30, it is considered that the carbonaceous material used in the manufacturing method of the joined steel member, which will be described later, is sufficiently diffused to the stainless steel member 10 side. Therefore, since carbides are unlikely to precipitate at the joint interface 30, the joined steel member 1 is considered to have high tensile strength and elongation.

[0011] The carbon concentration at the joint interface 30 in the joined steel member 1 according to this embodiment can be measured by cutting the joined steel member 1 along the joint interface 30, polishing the cross section, and measuring the carbon concentration using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX). In the present invention, the carbon concentration at the joint interface 30 is calculated by averaging measurements taken at any five points on the polished cross section.

[0012] The carbon concentration of the first concentration gradient layer 15 and the second concentration gradient layer 25 in the steel joint 1 according to this embodiment can be measured by cutting the steel joint 1 along the joint interface 30, then further cutting it in a direction away from the surface of the cut joint interface 30 (towards the materials 10 and 20), and then polishing the cross section cut in the direction away, and measuring the carbon concentration using an element distribution measuring device such as an electron probe microanalyzer (EPMA) or an energy dispersive X-ray analyzer (EDX).

[0013] In the present invention, the tendency for the carbon concentration to increase or decrease in the first concentration gradient layer 15 and the second concentration gradient layer 25 can be measured by measuring the carbon concentration at any five points (10 points in total) on a straight line from the carbon concentration at the bonded interface 30 to the carbon concentration at the materials 10 and 20 in each direction from the bonded interface 30 to the materials 10 and 20 on a polished cross section in the separating direction using an element distribution measuring device as described above, and creating a graph as shown in FIG. 1 in which the carbon concentration is plotted against the distance, with the distance from the bonded interface 30 on the horizontal axis and the carbon concentration on the vertical axis.

[0014] In the steel joined body 1 according to the present embodiment and the manufacturing method thereof described later, the stainless steel material (raw material) 10 is, for example, an austenitic stainless steel specified by JIS, such as SUS304, SUS316, SUS304L, SUS316L, etc. The chromium-molybdenum steel material 20 refers to steels (SCM435H, etc.) designated by the symbols SCr and SCM in the standards. It is preferable that the stainless steel material (base material) 10 is SUS304, and the chromium-molybdenum steel material 20 is SCM435H. By using SUS304 and SCM435H as the materials to be joined, it is possible to reliably obtain a steel joint that achieves high tensile strength and elongation.

[0015] The shapes of the stainless steel material 10 and the chromium-molybdenum steel material 20 before joining are not particularly limited as long as they each have a joining surface and can be integrated with each other by overlapping these joining surfaces. The stainless steel material 10 and the chromium-molybdenum steel material 20 can be, for example, a cylindrical shape, a rectangular column shape, a screw shape, a concave-convex shape, etc.

[0016] FIG. 2 is a process flow diagram for explaining the method for manufacturing a steel member joint according to this embodiment. The method for producing a steel joined body according to this embodiment is a method for producing a steel joined body in which a stainless steel material and a chromium-molybdenum steel material are joined, as shown in FIG. 2, and includes an arrangement step S100 of arranging a carbonaceous material on at least one of the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined, a superposition step S110 of superposing the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined described above on each other via the carbonaceous material, and a heating step S120 of heating the stainless steel material and the chromium-molybdenum steel material with the superposed joining surfaces on each other at a maximum attainable temperature of 1300° C. or more and 1500° C. or less. The method for producing a steel member joint according to the present invention includes the above-described process flow, and thus can achieve high tensile strength and elongation in the joint between a stainless steel material and a chromium-molybdenum steel material.

[0017] Each of these steps will now be described in detail. Fig. 3 is a conceptual diagram for explaining a method for manufacturing a joined steel member according to a specific first embodiment of the present invention. Fig. 4 is a conceptual diagram for explaining a method for manufacturing a joined steel member according to a specific second embodiment of the present invention. The first embodiment shown in Fig. 3 and the second embodiment shown in Fig. 4 differ only in the form of the carbonaceous material placed on the joining surfaces of the stainless steel members.

[0018] <Regarding the placement process S100> In the manufacturing method of the joined steel material according to the present embodiment, in a disposing step S100, as shown in Fig. 3(a) and Fig. 4(a), a carbonaceous material (35 (powdered carbonaceous material) or 40 (sheet-like carbonaceous material: hereinafter also referred to as a graphite sheet) is disposed on at least one of the joining surfaces (10a and / or 20a: one of the joining surfaces in Fig. 3(a) and Fig. 4(a)) of the stainless steel material 10 and the chromium-molybdenum steel material 20 to be joined.

[0019] The carbonaceous materials 35, 40 can be disposed on at least one of the joining surfaces (10a and / or 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 to be joined, and the material and shape are not particularly limited as long as these joining surfaces (10a and 20a) can be integrated. For example, a powdered carbonaceous material 35 shown in FIG. 3 or a sheet-like carbonaceous material 40 shown in FIG. 4 can be used. Here, when a powdered carbonaceous material 35 is used, it can be disposed by applying it to the joining surfaces (10a and / or 20a). When a sheet-like carbonaceous material 40 is used, it can be disposed directly on the joining surfaces (10a and / or 20a) via, for example, double-sided tape or the like.

[0020] <About the overlapping step S110> In the manufacturing method of the joined steel body according to the present embodiment, in a superposing step S110, the joining surfaces (10a and 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 to be joined are superposed on each other via the carbonaceous material (35 or 40) arranged in the arrangement step S100, as shown in Fig. 3(b) and Fig. 4(b). In this superposing step S110, when the joining surfaces (10a and 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 are superposed on each other, it is preferable to apply a load to fix the joining surfaces to each other. In the overlapping process S110 of this embodiment, by applying a load to fix the joining surfaces (10a and 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 together, it is possible to increase the tensile strength and elongation at the joint between the stainless steel material 10 and the chromium-molybdenum steel material 20.

[0021] <About the heating step S120> In the manufacturing method of the steel material joint according to this embodiment, in the heating step S120, the stainless steel material 10 and the chromium-molybdenum steel material 20 whose joining surfaces (10a and 20a) have been overlapped in the overlapping step S110 are heated as shown in Figures 3(c) and 4(c).

[0022] In addition, in this heating step S120, it is preferable to apply a load to fix the joining surfaces (10a and 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 to each other when the heating is performed. In the heating process S120 of this embodiment, by applying a load to fix the joining surfaces (10a and 20a) of the stainless steel material 10 and the chromium-molybdenum steel material 20 together, the tensile strength and elongation at the joint between the stainless steel material 10 and the chromium-molybdenum steel material 20 can be increased.

[0023] The heating is performed at a maximum temperature of 1300° C. or more and 1500° C. or less. If the heating temperature is less than 1300° C., carbides may precipitate due to the low heating temperature, and the tensile strength and elongation may decrease. If the heating temperature exceeds 1500° C., other members that fix the steel joint may be thermally deformed during heating, and heating may not be optimal.

[0024] Fig. 5 is an iron-carbon phase diagram (corresponding to SUS304) for explaining the effect of the present invention when the heating temperature is 1300°C or higher. Fig. 6 is an iron-carbon phase diagram (corresponding to SCM435H) for explaining the effect of the present invention when the heating temperature is 1300°C or higher. Fig. 7 is a conceptual diagram for explaining the effect of the present invention when the heating temperature is 1300°C or higher.

[0025] In the manufacturing method of the steel joined body according to this embodiment, carbon powder (carbonaceous material) is placed on at least one of the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined, and the stainless steel material and the chromium-molybdenum steel material, which have been overlapped with each other with the carbonaceous material interposed therebetween, are heated in a predetermined atmosphere (e.g., in a nitrogen atmosphere) at a maximum temperature of 1300°C or more and 1500°C or less (see FIG. 7(a)).

[0026] First, the stainless steel side will be described with reference to FIG. When the temperature of the joining surface on the stainless steel side reaches 1300°C, a liquid phase (hereinafter referred to as "L") with a carbon concentration of 2.5 mass% is generated at the interface between the steel and the carbonaceous material (see the part indicated by the square in Figure 5). This liquid phase L increases until the carbonaceous material disappears (see Figure 7(b)). At 1300°C, the carbon concentration at the interface between the "liquid phase L+FCC (austenite phase)" region and the "austenite phase" region (see the part marked with a circle in Figure 5) is 0.5 mass% (see Figure 5). Carbon diffusion at 1300°C is extremely fast, and when maintained at this temperature, carbon diffuses at a high speed from the joining surface of the steel materials into the internal austenite phase. As a result, at the interface between the liquid phase L and the austenite, the austenite phase side tries to maintain the carbon concentration at 0.5 mass%, stealing carbon from the liquid phase L side. Meanwhile, the liquid phase L tries to maintain the carbon concentration at 2.5 mass%, so the liquid phase L decreases (see Figure 7(c)). Finally, the liquid phase L disappears and the joining of the steel materials is completed (see Figure 7(d)). Furthermore, by setting the maximum temperature to 1300° C. or higher, the generation (precipitation) of carbides and the like (for example, precipitation of α (M7C3: carbide) in FIG. 5) in the joint 50 during the heating step S120 can be suppressed.

[0027] Next, the chromium-molybdenum steel side will be described with reference to FIG. When the temperature of the joining surface on the chromium-molybdenum steel side reaches 1300°C, a liquid phase (hereinafter referred to as "L") with a carbon concentration of about 2.9 mass% is generated at the interface between the steel and the carbonaceous material (see the part indicated by the square in Figure 6). This liquid phase L increases until the carbonaceous material disappears (see Figure 7(b)). At 1300° C., the carbon concentration in the portion indicated by a circle in FIG. 6 is approximately 1.35 mass % (see FIG. 6).

[0028] As a result, the carbon concentration on the chromium-molybdenum steel side (square in Fig. 6: approximately 2.9 mass%, circle: approximately 1.35 mass%) is higher than the carbon concentration on the stainless steel side (square in Fig. 5: approximately 2.5 mass%, circle: approximately 0.5 mass%). Therefore, the carbon on the chromium-molybdenum steel side diffuses into the stainless steel side, which has a lower carbon concentration. As a result, a steel joined body is obtained in which a stainless steel material and a chromium-molybdenum steel material are joined, and the carbon concentration on the stainless steel material side at the joining interface between the stainless steel material and the chromium-molybdenum steel material is higher than the carbon concentration of the stainless steel material material, and the carbon concentration on the chromium-molybdenum steel material side at the joining interface is lower than the carbon concentration of the chromium-molybdenum steel material material. In addition, it is considered that this steel joined body can suppress the generation (precipitation) of carbides at the joining interface 30. Therefore, it is considered that high tensile strength and elongation can be achieved in the joining of the stainless steel material and the chromium-molybdenum steel material. Furthermore, since the maximum reaching temperature is 1300°C or more (i.e., a temperature higher than the temperature at which M7C3 (carbide) is generated (precipitated) in the iron-carbon phase diagram (corresponding to SUS304) in FIG. 5), it is considered that the generation (precipitation) of carbides at the joining interface 30 can be suppressed.

[0029] The heating means in the heating step S120 is not particularly limited as long as it does not impair the effects of the present invention, and various heating methods can be used, such as high-frequency induction heating 100 using a conventionally known heating coil 60, a heating furnace other than high-frequency induction heating, laser heating, etc. Furthermore, the atmosphere during heating in the heating step S120 is not particularly limited. The atmosphere includes, for example, an oxidizing atmosphere (oxygen, air, etc.) and a non-oxidizing atmosphere (nitrogen, argon, etc.).

[0030] The heating step S120 of the present invention is preferably performed by high-frequency induction heating 100. Since the high-frequency induction heating 100 can accurately and rapidly heat to a desired temperature, it is easy to manufacture the above-mentioned joined steel body 1.

[0031] Then, in the heating step S120 of the present invention, when the liquid phase L generated at the joining surface 50 (joint interface 30) of the stainless steel material 10 and the chromium-molybdenum steel material 20 disappears, the steel materials (10 and 20) are joined together (FIGS. 3(d) and 4(d)). The cooling means after the heating in the heating step S120 of the present invention is not particularly limited, and conventionally known gas cooling, spray cooling using a coolant such as a polymer, natural cooling, etc. can be used.

[0032] The maximum temperature reached in the heating step S120 of the present invention can be measured by a platinum-rhodium thermocouple welded to the outer circumferential surface of the steel material (raw material) side within 2 mm from the joining surface 50 of the stainless steel materials to be joined.

[0033] The present invention will now be described in more detail with reference to examples and comparative examples, although the present invention is not limited to these examples in any way. EXAMPLES

[0034] (Example) In Example 1, SUS304 having the chemical composition (unit: mass%) shown in Table 1 and SCM435H having the chemical composition (unit: mass%) shown in Table 2 were prepared in a cylindrical shape (length X: 150 mm, diameter T: 15 mm (50 mm diameter at joining surface)) as shown in FIG. 1.

[0035] [Table 1]

[0036] [Table 2]

[0037] Then, as a test specimen, the respective joining surfaces of the SUS304 and SCM435H were joined together to produce a steel joint as shown by reference number 1 in Fig. 1. At this time, a graphite sheet (graphite thickness 10 μm, double-sided tape thickness 6 μm: total thickness 16 μm) was placed on the joining surface of the SCM435H, and the joining surfaces of the SUS304 and SCM435H to be joined via this carbonaceous material were overlapped. Next, high-frequency induction heating was performed in a nitrogen gas atmosphere at a frequency of 6.6 kHz, a pressurizing pressure of 6.9 MPa, and a maximum temperature of 1300°C, and then the steel was allowed to cool.

[0038] (Comparative Example) A steel joint as shown by reference numeral 1 in FIG. 1 was produced under the same conditions as in Example 1, except that the maximum temperature was set to 1200° C.

[0039] For the test specimens (steel joints) produced in the above examples and comparative examples, a tensile test was performed at the joint interface 30. The tensile test was carried out in air at room temperature using an Instron tensile tester with a crosshead displacement rate of 5 mm / min. The load-displacement curve obtained from the tensile test was converted into a nominal stress-nominal strain curve to determine the tensile strength (MPa). In addition, a true stress-true strain curve and a work hardening rate-true strain curve were obtained from the nominal stress-nominal strain curve, and the elongation (%) was calculated from the intersection of each curve. A nominal stress vs. elongation (%) curve was also created.

[0040] FIG. 8 is a graph showing the results of the tensile strength, elongation, and elongation-nominal stress curves in the tensile tests of the examples and comparative examples. From FIG. 8, it can be seen that the comparative example had a tensile strength of 370 MPa and an elongation of 2.1%, while the example had a tensile strength of 506 MPa and an elongation of 11.0%, showing high tensile strength and elongation.

[0041] Next, the carbon content and hardness distribution at the joint interface between SUS304 and SCM435H in each of the examples and comparative examples were measured using an EPMA surface analyzer at an accelerating power of 15 kV and a sample current of 0.2 μA. FIG. 9 is a graph showing the carbon amount and hardness distribution at the joint interface in the example and the comparative example, measured by an EPMA surface analysis device. 9, in the comparative example, a high carbon content of about 20 mass% was confirmed on the SUS304 side of the bonded interface, and a high carbon content of about 2 mass% was also confirmed on the SCM435H side of the bonded interface. These are considered to be carbides.

[0042] On the other hand, in the examples, a high carbon content as in the comparative examples was not observed, and the carbon content was about 0.4 mass% on the SUS304 side of the bond interface, and further, on the SCM435H side of the bond interface, a concentration gradient layer (reference numeral 25 in FIG. 1 ) in which the carbon concentration decreases from the SCM435H material toward the bond interface was observed, i.e., the carbon concentration was lower than that of the SCM435H material, and no generation (precipitation) of carbides was observed. Therefore, it is believed that high tensile strength and elongation were achieved in the examples. [Industrial Applicability]

[0043] According to the joined steel material and the manufacturing method thereof of the present invention, high tensile strength and elongation can be achieved in the joining of a stainless steel material and a chromium-molybdenum steel material. Therefore, the steel joint according to the present invention can be suitably used for motor shafts (the pipe part is made of SUS304, which has high corrosion resistance, since it carries cooling water, and the shaft part is made of SCM, since high strength is required). [Explanation of symbols]

[0044] 1 Steel joint 10 Stainless steel material (material) 10a Joint surface 15 1st concentration gradient layer 20 Chromium molybdenum steel (material) 20a Joint surface 25 Second concentration gradient layer 30 Joint interface 35 Carbonaceous materials 40 Carbonaceous materials 50 Joint 100 High frequency induction heating S100 placement process S110 Layering process S120 Heating process A Carbon concentration (joint interface) B Carbon concentration (opposite side of the concentration gradient layer from the bonding interface) C Carbon concentration (chromium molybdenum steel material) T diameter (steel material) L liquid phase

Claims

1. A steel joint in which a stainless steel material and a chromium-molybdenum steel material are joined, A steel joint, wherein a carbon concentration on the stainless steel side at a joint interface between a stainless steel material and a chromium-molybdenum steel material is higher than a carbon concentration in a base material of the stainless steel material, and a carbon concentration on the chromium-molybdenum steel side at the joint interface is lower than a carbon concentration in a base material of the chromium-molybdenum steel material.

2. A method for manufacturing a steel joint in which a stainless steel material and a chromium-molybdenum steel material are joined, comprising the steps of: A disposing step of disposing a carbonaceous material on at least one of the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined; a lamination step of laminating the joining surfaces of the stainless steel material and the chromium-molybdenum steel material to be joined together via the carbonaceous material; and a heating step of heating the stainless steel material and the chromium-molybdenum steel material with their joining surfaces overlapped to a maximum temperature of 1300°C or higher and 1500°C or lower.

Citation Information

Patent Citations

  • Diffusion brazing method of steel

    JP1982022867A

  • Hot joining method for steel

    JP1994007970A

  • Method for producing steel material conjugant

    JP2023039175A